DISTRIBUSI SUMBING BIBIR DAN LANGIT-LANGIT DI CLEFT LIP AND PALATE CENTER FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH MALANG INDONESIA - Riana A, Ruby (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2015)
Objective: The purpose of this study was to investigate the distribution of different cleft pattern by the age of first operation, sex, side of cleft of Cleft Lips (CL), cleft palate (CP) and cleft lip and palate patients (CLP), and education level parents in Cleft Lip and Palate Center in Faculty of Medicine, University of Malang Muhammadiyah (CLPC FM UMM). Study design: Four hundred twenty-nine patients attending the CLPC FM UMM from January 2014 to December 2016 were studied. Most patients came from East Java, Indonesia and the surrounding areas. Result: Highest frequency of CL in CLPC FM UMM is in the age group 0-1 y.o, CP patients in the age group 1-5 y.o , while most CLP patients in the age group 1-5 y.o. Cleft lip and palate (61.31%) was most frequently found, followed by cleft lip with or without alveolus (33.33%) and cleft palate (5.36%). Cleft lip and palate, cleft lip with or without alveolus and cleft palate occurred more frequently in males. Left-sided unilateral clefts were observed in 57.34% of patients compared to right-sided unilateral clefts in 21.21%, the rest is bilateral cleft 21.45%. The unilateral complete CLP (45.22%) was most frequently found, followed by the unilateral incomplete CL (18.41%). Most of the parent?s education were elementary school graduated.Conclusion: The most frequent profile in the affected population were males, left sided unilateral complete CLP were most affected.